Teaching Writing to Eighth Grade Students Using Semantic Mapping - Basuni, Ahmad; Hartati, Sri (Journal of English Education, 2024)
This study investigates the effectiveness of semantic mapping as a teaching strategy to enhance the writing skills of eighth-grade students at SMPN 1 Bumi Agung. Semantic mapping, a visual tool that illustrates relationships between concepts, is hypothesized to aid students in organizing their thoughts and generating ideas for writing. The research employs a quantitative method through quasi-experimental design, collecting data by using writing test and analysing data with pre-test and post-test assessments to evaluate the impact of semantic mapping on students' writing proficiency. Results indicate a significant improvement in the writing abilities of students who were taught using semantic mapping compared to those who received traditional instruction. The findings suggest that semantic mapping is a valuable pedagogical tool in teaching writing to middle school students.